Economic Value of Recreational Benefits from the Mudumalai Tiger Reserve, Tamil Nadu, India: An Individual Travel Cost Approach. Issue 1 (June 2022) - Rajkumar, V.; Boopathi, S.
The study reported in this article estimates the economic value of recreational benefits of the Mudumalai Tiger Reserve (MTR) in the Nilgiris district of Tamil Nadu, and its determinants using the Individual Travel Cost Method. The tiger reserves in India account for more than a half of the world's tiger population and are providing a variety of ecosystem services. Most of these services, recreational services in particular, are non-marketed in nature. Hence, the economic value of the recreation services needs to be measured so that the public's scarce resources can be allocated efficiently for future protection, planning and managing the tiger reserves. Based on the information from primary surveys, our estimated result indicates that the annual recreational value of the MTR is equivalent to ₹114.26 million. The study also found that travel cost, respondent income, family size, gender and site quality are the most important determinants of demand for recreation at MTR. This implies that the recreational value generated by the MTR is significant and more investment in the reserve will enhance future recreational benefits as well as various other ecosystem benefits.